THE EFFECT OF TOTAL PHYSICAL RESPONSE (TPR) IN TEACHING ENGLISH VOCABULARY - Amrin Hi. Sabban; Jusmin H.J. Wahid; Nurmi Marisalawerang (Universitas Khairun, 2021)
The objective of this research is to know whether the use of Total Physical Response in teaching vocabulary competence. This research used quantitative method especially pre-experimental design trough pre-test and post-test. The data were collected by the researchers used three steps namely pre-test, treatment, and post-test. The researcher used vocabularies test to know the students' competence. Then, the researcher applied Total Physical Response to know the students' competence in mastering vocabulary. The result of the data indicates that the use of Total Physical Response can improve students' vocabulary competence. It can be seen in the result of pre-test=1050 and post-test=1348. The result of statically analysis of the level significance 0, 05 with the presented t-count=8, 3 is higher than t-table value=1,761. It means that the null hypothesis is rejected and it can improve students' vocabulary compotence. It can be stated that Total Physial Response is one of the affective way to iimprove students' vocabulary compotence.